Introduction to family medicine - Md Aris, Mohd Aznan; Azmi, Nurul Husna (IIUM Press, 2022)
Primary care (also known as family medicine as a medical speciality in primary care) is the first point of contact that an individual has with health care provision. Primary care doctors are known as family doctors, general practitioners or family physicians. Family medicine is a medical speciality that provides comprehensive and continuous health care for the individual and the whole family. The practise encompasses the biological, clinical aspect and behavioural sciences, whereas the scope covers all ages from womb to tomb, all sexes, all aspects of the organ system and all diseases.